Crop diversification can contribute to disease risk control in sustainable biofuels production. Issue 10 (1st December 2015) - Smith, Val H; McBride, Robert C; Shurin, Jonathan B; Bever, James D; Crews, Timothy E; Tilman, G David
Abstract : Global demand for transportation fuels will increase rapidly during the upcoming decades, and concerns about fossil‐fuel consumption have stimulated research on renewable biofuels that can be sustainably produced from biological feedstocks. However, if unchecked, pathogens and parasites are likely to infect these cultivated biofuel feedstocks, greatly reducing crop yields and potentially threatening the sustainability of renewable bioenergy production efforts. In particular, clonal biofuel crops grown as monocultures at industrial scales will be confronted both by an accumulation of specialist pathogens over time, and by the rapid evolution of those pathogens. We propose possible solutions to these important sustainability problems, with a focus on managing disease risk through crop rotations and the cultivation of multi‐species polycultures.